Power Law Fluid Gravity Fluctuations on Dual Component Convection in a Porous Channel in Presence of Throughflow - N, Manjunatha (Iraqi Journal of Science, 2025)
This study investigates the instability of power-law fluids in a porous channel, emphasizing dual component convection influenced by gravity variations and vertical throughflow. A single-term Galerkin approximation is employed to derive critical Rayleigh numbers and neutral stability curves. The findings reveal that the power-law index tends to destabilize the system, affecting the neutral stability curves, while buoyancy forces contribute to enhancing stability. The role of gravity variations is highlighted as a critical factor, with exponential-type fluctuations proving more effective at achieving stability compared to linear-type fluctuations. Overall, the study emphasizes that key parameters, including the power-law index, buoyancy force, and gravity variations, have a substantial impact on the system's stability characteristics.